Joyful Learning and Students’ Motivation in Islamic Religious Education at SDN 27 Pinrang - Khairunnisa Khairunnisa; Salmiati Salmiati; Nurlina Jalil (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
The low learning motivation of students in Islamic Religious Education at the elementary school level is often caused by monotonous, traditional, and teacher-centered learning methods that limit students’ active participation. This condition makes students less enthusiastic and less engaged in the learning process. This study aims to examine the implementation of the Joyful Learning method and its impact on students’ learning motivation in Islamic Religious Education (IRE) at SDN 27 Pinrang. This study used a descriptive qualitative approach. The results showed that implementing Joyful Learning through educational games, active discussions, group work, creative media, and contextual learning increased students’ motivation, enthusiasm, participation, and understanding. This method created a pleasant learning atmosphere, reduced boredom, and strengthened positive relationships between teachers and students. Also, it can improve students’ intrinsic and extrinsic motivation and support their cognitive, emotional, moral, and spiritual development in IRE.